Vaccines against human papillomavirus in low and middle income countries: - Nakalembe, Miriam; Mirembe, Florence M.; Banura, Cecily (Cross Mark, 2015)
Abstract Currently, there is limited data on the immunogenicity and efficacy of human papillomavirus vaccines in Low and Middle income countries (LMIC). The review aims to summarize the current status from published HPV vaccine safety, immunogenicity and efficacy studies in low and middle income countries (LMIC). Electronic databases (PubMed/MEDLINE and HINARI) were searched for peer reviewed English language articles on HPV vaccination in LMIC that have so far been published from 1st January 2006 up to 30th January 2015. Eligible studies were included if they had used the bivalent (bHPV) or quadrivalent HPV (qHPV) vaccines in a LMIC and investigated safety, immunogenicity and/or efficacy. The main findings were extracted and summarized. A total of fourteen HPV vaccine studies assessing safety, Immunogenicity and efficacy of the bivalent or quadrivalent vaccines in LMIC were included. There are only ten published clinical trials where a LMIC has participated. There was no published study so far that assessed efficacy of the HPV vaccines in Sub-Saharan Africa. From these studies, vaccine induced immune response was comparable to that from results of HICs for all age groups. Studies assessing HPV vaccine efficacy of the bivalent or quadrivalent vaccine within LMIC were largely missing. Only three studies were found where a LMIC was part of a multi center clinical trial. In all the studies, there were no vaccine related serious adverse events. The findings from the only study that investigated less than three doses of the bivalent HPV-16/18 vaccine suggest that even with less than three doses, antibody levels were still comparable with older women where efficacy has been proven. The few studies from LMIC in this review had comparable safety, Immunogenicity and efficacy profiles like in HIC. Overall, the LMIC of Africa where immune compromising/modulating situations are prevalent, there is need for long term immunogenicity as well as surveillance studies for long term clinical effectiveness after two and three dose regimens. Keywords: Human papillomavirus vaccines, Immunogenicity, Safety, Efficacy, Low middle income countries
a review of safety, immunogenicity and efficacy
Keywords: Vaccines; human papillomavirus; low and middle income countries; safety, immunogenicity and efficacy